2021
DOI: 10.1002/aic.17212
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fouling by lysozyme: Effect of local interaction

Abstract: Molecular dynamics simulations were performed to understand the adsorption of positive‐charged lysozyme onto negative‐charged polyvinylidene fluoride membrane at three pH and two ionic strengths. The lysozyme was initialized at six orientations at 10 Å from the membrane and adsorption was deemed to occur when the lysozyme is less than 4 Å from the membrane. Local interactions are clearly important: (i) despite opposite net charges, no adsorption occurs in some cases throughout; (ii) lysozyme‐membrane separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…67−69 On one hand, for the same foulant, because of the similar extents of hydration in different environments, the flux trend can be directly correlated with foulant−membrane interaction energy. 67,68 On the other hand, when different foulants are compared, the more significantly different extents of hydration have non-negligible influences on the overall free energy, and thereby the foulant−membrane energy is not directly correlated with the flux trends. 69 In this study, three surfactants have distinctly different hydrations (Figure 7a), which necessitates the consideration of the overall free energy.…”
Section: Resultsmentioning
confidence: 99%
“…67−69 On one hand, for the same foulant, because of the similar extents of hydration in different environments, the flux trend can be directly correlated with foulant−membrane interaction energy. 67,68 On the other hand, when different foulants are compared, the more significantly different extents of hydration have non-negligible influences on the overall free energy, and thereby the foulant−membrane energy is not directly correlated with the flux trends. 69 In this study, three surfactants have distinctly different hydrations (Figure 7a), which necessitates the consideration of the overall free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the orientation of the protein, metastable states are known to be attained instead of the minimum energy state 54 . To account for such variations, the simulations for each protein were initialized using one of six orientations, which are 90° rotations about the x ‐axis or y ‐axis, as per earlier studies 33,53 . Such multiple different orientations allow for different domains of the macromolecular protein to interact with the membrane initially.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Horinek et al 32 studied the desorption of peptide chains from a hydrophobic diamond surface and concluded that the intimate coupling of dispersive and solvation effects are important for adsorption behavior. Our earlier study focused on the adsorption behavior of lysozyme onto the membrane under different pH and salt concentrations, and demonstrated that local interactions are important in affecting lysozyme–membrane interactions 33 . A question that remained unaddressed was the different adsorption behaviors of proteins of positive versus negative net charges, which is what motivated the current study.…”
Section: Introductionmentioning
confidence: 98%
“…The biological interface phenomenon is widely encountered in life and physical sciences, as well as in medicine and biotechnology, primarily arising from the complex behavior of biomolecules on or in close vicinity of solid–liquid interfaces, controlled by a delicate mixture of molecular interactions. To regulate the interfacial behavior of biomolecules, a thorough understanding of the complex process is of great importance, and the mechanisms behind proteins interacting with solid surfaces have long been scrutinized experimentally since 1980s. Several factors can influence the protein interfacial behavior, including the properties of proteins (e.g., surface charge distribution, structural conformation, and size), , the properties of substrates (e.g., geometric topography, surface chemical composition, and properties), , and external environmental factors (e.g., pH, ionic strength, and temperature) . Among all these impactors, the ions in the solution play an important role as they affect the properties of the solution itself, including the viscosity and surface tension of aqueous solutions, and also those related to the proteins, such as the solubility, stability, and surface charge of proteins. , Furthermore, the buffer ions affect biological processes, including enzyme activities, bacterial growth, protein nonspecific adsorption, and biodetection …”
Section: Introductionmentioning
confidence: 99%